Interventions to Improve Safer Sleep Practices in Families With Children Considered to Be at Increased Risk for Sudden Unexpected Death in Infancy: A Systematic Review - Ellis, Catherine; Pease, Anna; Garstang, Joanna; Watson, Debbie; Blair, Peter S.; Fleming, Peter J. (Frontiers in Pediatrics, 2022)
Background Advice to families to follow infant care practices known to reduce the risks of Sudden Unexpected Death in Infancy (SUDI) has led to a reduction in deaths across the world. This reduction has slowed in the last decade with most deaths now occurring in families experiencing social and economic deprivation. A systematic review of the literature was commissioned by the National Child Safeguarding Practice Review Panel in England. The review covered three areas: interventions to improve engagement with support services, parental decision-making for the infant sleep environment, and interventions to improve safer sleep practices in families with infants considered to be at risk of SUDI. Aim To describe the safer sleep interventions tested with families with infants at risk of SUDI and investigate what this literature can tell us about what works to reduce risk and embed safer sleep practices in this group. Methods Eight online databases were systematically searched in December 2019. Intervention studies that targeted families with infants (0-1 year) at increased risk of SUDI were included. Studies were limited to those from Western Europe, North America or Australasia, published in the last 15 years. The Quality Assessment Tool for Studies with Diverse Designs was applied to assess quality. Data from included studies were extracted for narrative synthesis, including mode of delivery using Michie et al’s (2014) Mode of Delivery Taxonomy. Results The wider review returned 3367 papers, with 23 intervention papers. Five types of intervention were identified: (1) infant sleep space and safer sleep education programmes, (2) intensive or targeted home visiting services (3) peer educators/ambassadors (4) health education / raising awareness interventions (5) targeted health education messages using digital media. Conclusion Influencing behaviour in families with infants at risk of SUDI has traditionally focussed on ‘getting messages across’, with interventions predominantly using education and awareness raising mechanisms. This review found evidence of interventions moving from ‘information giving’ to ‘information exchange’ models using personalised, longer term relationship-building models. This shift may represent an improvement in how safer sleep advice is implemented in families with infants at risk, but more robust evidence of effectiveness is required.